A novel Cu–Mn/Ca–Zr catalyst for the synthesis of methyl formate from syngas. Issue 83 (9th September 2015) - Zhao, Haijun; Lin, Minggui; Fang, Kegong; Zhou, Juan; Liu, Ziyu; Zeng, Gaofeng; Sun, Yuhan
<x xml:space="preserve">Abstract</x> A novel catalyst comprised of Cu–Mn mixed oxides and CaO–ZrO2 solid base has contributed to a high-performance methyl formate (MF) synthesis from syngas in a slurry reactor.